Analisis Faktor-Faktor Yang Mempengaruhi Pertumbuhan Ekonomi Di Kota Batam - Haposan Banjarnahor; Syahril Effendi (LPPM Universitas Putera Batam, 2022)
The economy is said to experience growth if the level of economic activity achieved is now higher than that achieved in the previous period. Growth is achieved if the physical quantity of goods and services produced in the economy increases from the previous years. The purpose of this study is to examine and further examine the effect of Investment and Regional Original Income (PAD) on economic growth. The population of this study is Investment and Regional Original Revenue (PAD) found in BP Batam in 2016-2021. The sample selection technique in this study used Purposive sampling with certain criteria within 6 years. The data in this study are secondary data in the form of financial statements obtained through BP Batam and BP Batam's official website. The data analysis method used is multiple linear regression method. The results of this study indicate that partially Investment and Regional Original Income (PAD) does not affect economic growth. The results of the F test show that the Regional Original Investment and Accountability variables have no effect on economic growth.